Private equity challenge - market overview and sprouts farmers market´s investment thesis - Santos, Mariana Lima (2022)
This investment committee paper consists of a proposal for a leveraged buy out of Sprouts Farmers Market, a US-based supermarket chain, leader in the organic segment. The group has developed a value creation strategy based on the expansion of store network and margins, through the exploration of efficiencies and a private label program. Under the proposed strategy and following a capital structure with 64,5% Entry Debt/EV, the deal will result in an IRR of 21,7% and a money multiple of 2.7x, over a 5-year investment period.